The ornithological collection at the University of Costa Rica: a perspective on historical and international collecting - Ocampo, Diego; Mason, Nicholas A.; Sandoval, Luis (Revista de Biología Tropical, 2025)
Introduction: Natural history collections play a vital role in research and education. However, their value and benefits are frequently overlooked, and the museum’s holdings tend to be unknown outside of museum personnel. Objective: We aim to evaluate and report the taxonomic and geographic coverage of the ornithological collections of the museum of zoology at the Universidad de Costa Rica (MZUCR). Methods: We estimated species-level and family-level representation across the six sub-collections of the collection of ornithology at MZUCR, and contrasted the taxonomic coverage and temporal patterns of the round-skin collection against other collections of Costa Rican birds housed in Costa Rica and abroad. Results: The eggs and nests collection represent only a small fraction of the Costa Rican breeding birds (569 nests from 128 species and 117 egg clutches from 78 species). The skeleton collection is the smallest with little growth over time (353 skeletons from 203 species). Tongues collection is growing (845 tongues from 329 species) and expected to fuel future research in comparative morphology. The tissue collection is the most recent and has the highest growth rate (1979 samples from 408 species), reflecting the importance of molecular studies in current research. The round-skin collection has the highest representation of the Costa Rican avifauna (5080 skins from 761 species), but it represents a small fraction of all the specimens collected in Costa Rica. Conclusion: These results highlight the importance of the MZUCR collection in documenting the Costa Rican avifauna, and its potential for ornithological research. However, the majority of species do not have the sufficient number of specimens required for robust population level studies. We underscore the importance of continuous growth and proper management of scientific collections for their use for future generations.